Pengaruh Lama Penyinaran Resin Komposit Nanofil Packable Terhadap Kekuatan Tekan (Compressive Strength) Bahan Restorasi - Karina, Era; , drg. Ana Riolina, MPH; , drg. Nanang Krisnawan (2014)
Nanofilled resin composites are recognized to combine the good mechanical strength of the hybrids and the best polish of the microfills. One of the mechanical properties that should be considered is compressive strength due to masticatory force on restoration. A resin composite is composed by organic polymer matrix, inorganic filler, coupling agent, and the initiator-accelerator system. Light activated resin composite polymerization is initiated by light cure unit. This process has complicated relationship with resin properties. One factor that can modulate the mechanical properties is exposure time therefore that should be watched the effect of exposure time on compressive strength of resin composite. For measuring the compressive strength, 5 specimens of each group were prepared in customized acrylic cylindrical mould of 8 x 4 mm and were exposured by light cure unit for 20s, 40s, and 60s. All specimens were immersed in artificial saliva and incubated at 37˚C for 24h. The compressive test was determined by loading using a Universal Testing Machine at a crosshead speed of 0.5mm/min. Results were statistically analysed using one-way ANOVA with 95 % confidence interval. Statistical result showed that exposure time has no effect on compressive strength of packable nanofilled resin composite (p > 0.05).